Central Pressure Waveform-Derived Indexes Obtained From Carotid and Radial Tonometry and Brachial Oscillometry in Healthy Subjects (2–84 Y): Age-, Height-, and Sex-Related Profiles and Analysis of Indexes Agreement - Zócalo, Yanina; Bia, Daniel (Frontiers in Physiology, 2022)
Aortic pressure (aoBP) waveform-derived indexes could provide valuable (prognostic) information over and above cardiovascular risk factors (CRFs). To obtain aoBP waveform-characteristics, several (i) techniques, (ii) recording sites, (iii) pressure-only waveform analysis mathematical approaches (e.g., pulse wave analysis (PWA), wave separation analysis (WSA)) and (iv) indexes (augmentation pressure (AP) and index (AIx), forward (Pf) and backward (Pb) components of aoBP, reflection magnitude (RM) and index (RIx)), were proposed. An accurate clinical use of these indexes requires knowing their physiological age-related profiles and the expected values for a specific subject. There are no works that have characterized waveform-derived indexes profiles in large populations considering: (i) as a continuous, data from different age-stages (childhood, adolescence, adulthood), (ii) complementary indexes, (iii) obtained from different techniques and approaches, and (iv) analyzing potential sex- and body height (BH)-related differences. In addition, (v) there is a lack of normative data (reference intervals, RIs) for waveform-derived indexes. Aims: (1) to evaluate the association and agreement between PWA- and/or WSA-derived indexes obtained with different techniques and approaches; (2) to determine the need for sex-, BH-, and/or age-specific RIs; (3) to define RIs for PWA- and WSA-derived indexes in a large cohort of healthy children, adolescents and adults. Methods: 3619 subjects (3-90 y) were included; 1688 healthy (2-84 y). AP, AIx, AIx@75, Pf, Pb, RM and RIx were obtained (carotid and radial tonometry, brachial oscillometry/plethysmography). The association and agreement between indexes was analyzed (Concordance correlation coefficients, Bland-Altman analysis). Mean and standard deviation equations and sex-specific BH- and age-related profiles were obtained (regression methods; fractional polynomials). Results: Waveform-derived indexes were not equivalent; for a specific index there were systematic and proportional differences associated with the recording site (e.g. carotid vs. radial) and technique (e.g., tonometry vs. oscillometry). The need for sex-, BH- or age-specific RIs was dependent on the index and/or age considered. RIs were defined for each index considering differences between recording sites and techniques. Equations for waveform-derived indexes age-related profiles were included, enabling to determine for a specific subject, the expected values and potential data deviations.